Optimal nutrient exchange and immune responses operate in partner specificity in the cnidarian-dinoflagellate symbiosis - Matthews, Jennifer L.; Crowder, Camerron M.; Oakley, Clinton A.; Lutz, Adrian; Roessner, Ute; Meyer, Eli; Grossman, Arthur R.; Weis, Virginia M.; Davy, Simon K. (Proceedings of the National Academy of Sciences - PNAS, 2017)
The relationship between corals and dinoflagellates of the genus Symbiodinium is fundamental to the functioning of coral ecosystems. It has been suggested that reef corals may adapt to climate change by changing their dominant symbiont type to a more thermally tolerant one, although the capacity for such a shift is potentially hindered by the compatibility of different host-symbiont pairings. Here we combined transcriptomic and metabolomic analyses to characterize the molecular, cellular, and physiological processes that underlie this compatibility, with a particular focus on Symbiodinium trenchii, an opportunistic, thermally tolerant symbiont that flourishes in coral tissues after bleaching events. Symbiont-free individuals of the sea anemone Exaiptasia pallida (commonly referred to as Aiptasia), an established model system for the study of the cnidarian-dinoflagellate symbiosis, were colonized with the “normal” (homologous) symbiont Symbiodinium minutum and the heterologous S. trenchii. Analysis of the host gene and metabolite expression profiles revealed that heterologous symbionts induced an expression pattern intermediate between the typical symbiotic state and the aposymbiotic state. Furthermore, integrated pathway analysis revealed that increased catabolism of fixed carbon stores, metabolic signaling, and immune processes occurred in response to the heterologous symbiont type. Our data suggest that both nutritional provisioning and the immune response induced by the foreign “invader” are important factors in determining the capacity of corals to adapt to climate change through the establishment of novel symbioses.